Sengketa Pemilukada Kotawaringin Barat (Analisis Terhadap Putusan MK No. 45/PHPU.D-VIII/2010 dari Perspektif Hukum Negara dan Hukum Islam) - Noorwahidah, Noorwahidah (Jurnal Konstitusi, 2011)
In addressing the problem Dispute of Election Results (PHPU) of West Kotawaringin, the Constitutional Court (MK) has made a controversial decision. The decision was not only disqualifying candidates, but also ordered the Local Election Commission to appoint elected mayor and deputy mayor. Some experts argue this decision exceeds the authority of the Court. Some other judge that the Court is correct. The Act does give authority to the Constitutional Court to try a PHPU case but not explicitly regulate and define the authority to disqualify a winner. Thus, this decision is an ijtihad of the judges. From the law and legislation of view the decision was not contrary to law. In the Islamic perspective, the decision was in line with maqashid ash-Sharia (Shari’a purposes).